Zero trust architecture - Green-Ortiz, Cindy; Fowler, Brandon; Houck, David; Hensel, Hank; Lloyd, Patrick; McDonald, Andrew; Frazier, Jason (Cysco Press, 2024)
Today's organizations need a new security model that more effectively adapts to the complexity and risks of modern environments, embraces hybrid workplaces, and protects people, devices, apps, and data wherever they're located. Zero Trust is the first model with the potential to do all that. Zero Trust Architecture: Theory, Implementation, Maintenance, and Growth is the first comprehensive guide for architects, engineers, and other technical professionals who want to move from Zero Trust theory to implementation and successful ongoing operation. A team of Cisco's leading experts and implementers offer the most comprehensive and substantive guide to Zero Trust, bringing clarity, vision, practical definitions, and real-world expertise to a space that's been overwhelmed with hype. The authors explain why Zero Trust identity-based models can enable greater flexibility, simpler operations, intuitive context in the implementation and management of least privilege security. Then, building on Cisco's own model, they systematically illuminate methodologies, supporting technologies, and integrations required on the journey to any Zero Trust identity-based model. Through real world experiences and case study examples, you'll learn what questions to ask, how to start planning, what exists today, what solution components still must emerge and evolve, and how to drive value in the short-term as you execute on your journey towards Zero Trust.